MENS REA TERHADAP DUGAAN TINDAK PIDANA DEFAMASI: PERSPEKTIF LINGUISTIK FORENSIK - Amal Akbar; Andika Wahyudi Gani; Anzar Anzar (Universitas Negeri Makassar, 2025)
This study aims to identify the mens rea element in the statements made by perpetrators of defamation in alleged defamation cases. This study uses a descriptive qualitative method with a pragmatic forensic linguistic approach. The data sources for this study are statements and legal documents contained in the Investigation Report of alleged defamation cases that occurred in the jurisdiction of the North Toraja Resort Police. The main data consists of transcripts of statements from witnesses and reported parties that were officially documented by investigators. Data collection was carried out through investigations and interviews with investigators. Data analysis was conducted using a forensic linguistic model with an emphasis on speaker meaning reconstruction. The results of the study show that the statement ‘You have deceived the Palawa people, that's why you came here, you deceiver, liar, thief’ contains linguistic indicators in the form of negative evaluative diction, declarative sentence structure, public context, and repetition of statements that reflect intentional encoding. The conclusion of the study confirms that mens rea can be identified objectively through forensic linguistic analysis, so that language can be used as empirical evidence in proving legal intent in defamation cases.